Pengaruh Implementasi Kampus Merdeka dan Persepsi Mahasiswa tentang MBKM terhadap Minat Mengikuti Program Merdeka Belajar Kampus Merdeka - Riyentin Zahra; Pujiati Pujiati; Widya Hestiningtyas (Jurnal Syntax Admiration, 2024)
This study aims to determine the factors that influence interest in participating in the Merdeka Belajar Kampus Merdeka program among students of Social Sciences Education. The method in this research uses descriptive quantitative with ex post facto and survey approaches. The population in this study were active students of Social Science Education class of 2020. The number of samples in this study totaled 153 students using a sampling technique stratified random sampling by using purposive sampling. Data collection using questionnaires and interviews. Data analysis uses multiple linear regression and multiple linear regression and is processed with the SPSS program. The results of this study indicate that there is an influence on the implementation of the independent campus and students perceptions of MBKM on the interest in participating in the Independent Learning Campus program among Social Sciences Education students with a determination level of 0.525 or 52.5% student interest is influenced by the implementation of an independent campus and students perceptions of MBKM, the remaining 47.5% is influenced by other factors not included in this model.